Anxiety and depression in the elderly during COVID-19: The moderating role of social media use - Santos Grau, Cinthya Martins dos; Menezes, João Daniel de Souza; Matheus Querino da Silva; Yuri Sacardo; Emerson Roberto dos Santos; Renato Mendonça Ribeiro; Natália Sperli Geraldes Marin dos Santos Sasaki; Vânia Del'Arco Paschoal; Daniele Alcalá Pompeo; Maria Cláudia Parro; Alba Regina de Abreu Lima; Vânia Maria Sabadoto Brienze; et al. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: To evaluate the use of social networks and other moderators in reducing anxiety and depression in the elderly during the Covid-19 pandemic and to correlate these factors with sociodemographic aspects. Methods: A cross-sectional study with a descriptive design, quantitative approach, and analytical type with correlation between variables. The research was conducted with 72 elderly individuals over 60 years of age. A sociodemographic health questionnaire, the Geriatric Anxiety Inventory (GAI), and the Geriatric Depression Scale (GDS-15) were applied. Blood pressure was measured at the time of the interview and compared with the average values from the previous year. Results:The elderly presented hypertension (69.44%) and anxiety (51.39%), with a higher incidence of anxiety in men (52.78%) with p=0.013. The elderly who used social networks showed significantly less depression than those who did not use them (p=0.015). Conclusions: Anxiety was more expressive than depression, and the elderly who used social networks were less depressed due to mutual support, experience sharing, and cognitive stimulation, factors that moderated the incidence of depression during the uncertainties of COVID-19. (www.actabiomedica.it)